The value of ecosystem services in global marine kelp forests - Eger, Aaron M. (2023)
While marine kelp forests have provided valuable ecosystem services for millennia, the global ecological and economic value of those services is largely unresolved. Kelp forests are diminishing in many regions worldwide, and efforts to manage these ecosystems are hindered without accurate estimates of the value of the services that kelp forests provide to human societies. Here, we present a global estimate of the ecological and economic potential of three key ecosystem services - fisheries production, nutrient cycling, and carbon removal provided by six major forest forming kelp genera (Ecklonia, Laminaria, Lessonia, Macrocystis, Nereocystis, and Saccharina). Each of these genera creates a potential value of between $64,400 and $147,100/hectare each year. Collectively, they generate between $465 and $562 billion/year worldwide, with an average of $500 billion. These values are primarily driven by fisheries production (mean $29,900, 904 Kg/Ha/year) and nitrogen removal ($73,800, 657 Kg N/Ha/year), though kelp forests are also estimated to sequester 4.91 megatons of carbon from the atmosphere/year highlighting their potential as blue carbon systems for climate change mitigation. These findings highlight the ecological and economic value of kelp forests to society and will facilitate better informed marine management and conservation decisions.